2020
DOI: 10.1186/s12964-020-00589-8
|View full text |Cite
|
Sign up to set email alerts
|

CCL2/CCR2 signaling in cancer pathogenesis

Abstract: Chemokines are a family of small cytokines, which guide a variety of immune/inflammatory cells to the site of tumor in tumorigenesis. A dysregulated expression of chemokines is implicated in different types of cancer including prostate cancer. The progression and metastasis of prostate cancer involve a complex network of chemokines that regulate the recruitment and trafficking of immune cells. The chemokine CCL2 and its main receptor CCR2 have been receiving particular interest on their roles in cancer pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(160 citation statements)
references
References 176 publications
(234 reference statements)
4
156
0
Order By: Relevance
“…However, recent studies have highlighted CCR2 as the primary driver of myelomonocytic recruitment during inflammation [ 35 ]. In addition, the importance of chemokines and their receptors in regulating anti-tumor immunity and tumor metastases were recently reviewed [ 36 , 37 , 38 ], including the dominant role of CCR2 in promoting recruitment of monocytes with pro-tumorigenic and pro-metastatic activities. Consistent with this, ongoing clinical trials have reported encouraging results of CCR2 inhibitors, especially as combination therapies, in patients with pancreatic cancers, hepatocellular carcinomas and ovarian cancers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have highlighted CCR2 as the primary driver of myelomonocytic recruitment during inflammation [ 35 ]. In addition, the importance of chemokines and their receptors in regulating anti-tumor immunity and tumor metastases were recently reviewed [ 36 , 37 , 38 ], including the dominant role of CCR2 in promoting recruitment of monocytes with pro-tumorigenic and pro-metastatic activities. Consistent with this, ongoing clinical trials have reported encouraging results of CCR2 inhibitors, especially as combination therapies, in patients with pancreatic cancers, hepatocellular carcinomas and ovarian cancers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine C-C motif ligand 2 (CCL2), is a well-known cytokine belonging to the CC chemokine family 9, which can affect drug sensitivity in both paracrine and autocrine manners ( Hao et al, 2020 ). CCL2 expression has been related to tumor invasion, metastasis, and drug resistance ( Zhong et al, 2018 ; Dutta et al, 2020 ; Hao et al, 2020 ). Xu et al (2018b) have found that DPP-resistant gastric cancer cell lines, such as BGC823/DDP cells and SGC7901/DDP cells secrete more CCL2 to maintain DDP resistance.…”
Section: Dual Roles Of Autophagy In Chemoresistance Of Gastric Cancermentioning
confidence: 99%
“…TAMs are believed to originate in the bone marrow as monocytes which are then recruited to the primary tumor via the CCL2/CCR2 signaling axis [ 29 ]. However, studies have shown that even tissue-resident macrophages derived from the YS or FL can be reprogrammed in-situ by signals derived from tumors cells.…”
Section: Tumor-associated Macrophages In Breast Cancermentioning
confidence: 99%